Collective treatment of the pairing hamiltonian IV. The Yrast approximation - Bés, Daniel; Dussel, G. G.; Maqueda, E.; Perazzo, R. P. J. (North Holland Publishing, 1973)
Fil: Bés, Daniel Comisión Nacional de Energía Atómica; Argentina